Testing Demographic Differences for Alcohol Use Initiation among Adolescents for the Decisional Balance and Situational Temptations Prevention Inventories - Sillice, Marie A. (2014)
Alcohol use by middle school-aged students is a public health concern because of the numerous adverse social, health and psychological outcomes. Prevention programs attempt to intervene before alcohol use begins. A tailored, computer-delivered program for the prevention of alcohol use and a series of new transtheoretical model measures were developed, including decisional balance (Pros and Cons) of alcohol use and Situational Temptations to Try Alcohol. This study investigated if there were any demographic differences on these measures in a sample of 6(th) grade middle school students from 20 schools (N=4151) at baseline. Three factorial analysis of variance tests were conducted to explore the impact of race (whites vs. non-whites), ethnicity (Hispanics vs. Non-Hispanics) and gender (males vs. females). A significant two-way interaction effect was found between gender and ethnicity for Pros of Alcohol Use. A significant three-way interaction effect was found between gender, race and ethnicity for Cons of Alcohol Use. Main effects were found for the three demographic factors for Situational Temptations to Try Alcohol. However, the effect sizes for the interaction effects and main effects were very small (all below η(2)=. 01), suggesting that race/ethnicity and gender alone may not be highly influential factors in the Decisional Balance for the Prevention of Alcohol and Situational Temptations to Try Alcohol in adolescence. The implications for these results and alcohol use prevention among this group are discussed.